(untitled) (Mongolian Journal of Agricultural Sciences, 2017)
The effect of different preceding crops, catch crops and manure application on the agronomic performance of potato was studied in two consequential years in an organic farming system. Within the study the effect of three different preceding crops: viz. lucerne, field pea and spring barley; incorporated catch crops as green manure: non-legume or mixture; and farmyard manure (30 tones ha-1) are tested on subsequent potato yield and tuber size distribution. The catch crop treatments were studied in comparison to control bare fallow. The subsequent crop response to preceding crops was negligible since there was no indication of a greater tuber yields (fresh tuber, marketable and dry matter) after legume pre-crops compared to barley. Catch crops and manure effects both slightly increased tuber dry matter yield from 4.9 tones ha-1 to 5.2 tones ha-1 in 2010 only, on the contrary dry matter yield was not affected by catch crop and manure in 2011. The significant interaction effect was found between year and catch crop for fresh and dry matter tuber yield and non-standard small sized tubers. Catch crops had a positive effect on potato yield only in 2010 when mineral nitrogen availability was low. The catch crops significantly (P < 0.01) increased the percentage of large sized tubers (> 65 mm in diameter); however catch crops even negatively affected potato medium sized tuber yield and quality. Significant (P < 0.01) interaction effect was found between year and catch crop for small sized tubers, also.